Sistematización de la experiencia práctica del diseño de evaluación de desempeño 180° para el personal de la Unidad Educativa William Blake, en el periodo marzo- junio 2017 - Caiza Anago, Diana Paola (2018)
The present titling project review the scheme and execution the instrument to evaluate performance of all the staff that belongs to “Unidad Educativa William Blacke”, being reference the importance whether in structural or functional of process and the unmatched benefit that you get for the institution. Measure the skills and abilities of the employee at his workplace with real results that allow to know the level of performance and the behaviors of the competences that they have in their functions to be able to actuate in the less time likely in the variable that needs to be improved attaining institutional and personal development. The primary objective is to know the skills of the staff with which the institution counts and be able to develop their skills and abilities in the case that is necessary, in this way the campaign worker will be trained to be able to provide a service of excellence at students and parents who belong to the institution and meet the expectations that they have in the high school. With the results obtained in the intervention project the results are analyze to verify impact, benefit and objectivity of the process maintain the evaluation a long term in the institution.